"Contemporary Indian urban society: ethnicity, gender and governance" - "Gill, Rajesh" (New Delhi, 2009)
his book fills a significant void in the field of urban sociology by addressing to the multidimensional issues concerning urbanizing societies, both rural and urban, with a special focus upon the socio cultural transformation, in Indian context. The various chapters take up both theoretical and empirical analyses on the issues such as urban planning and development, urban governance, women and urbanization, urban poverty and so on.
Keywords: Urbanisation